Optimasi Parameter Kinetika Pengeringan Buah Mengkudu (Morinda citrifolia) dengan Pendekatan Solver Tools - Ernawati Jassin; Imran Muhtar; Rahmawati Saleh; Luthfiah Luthfiah; Ilham Ahmad; Kusniati Kusniati (Lembaga Pengembangan Kinerja Dosen, 2025)
Noni (Morinda citrifolia L. (Rubiaceae) is a medicinal plant that contains bioactive compounds with antioxidant and antibacterial properties. More than 160 phytochemical components have been identified in noni plants, most of which are polyphenol and antioxidant compounds. The purpose of this study was to determine a mathematical model of thin-layer drying in maximizing the development that can identify the characteristics of noni fruit. This study used an experimental method with slicing thickness treatments, namely: 3 mm, 5 mm and 7 mm, the drying tool used was a cabinet dryer, different temperature treatments ranging from 45 oC, 55 oC and 65 oC, with different drying times, namely: 3 mm thickness for 14 hours, 5 mm thickness for 16 hours and 7 mm thickness for 17 hours. The observation data were analyzed using a mathematical approach to complete the calculation of the mathematical model, the moisture ratio value was applied to various mathematical models, namely: the Midili et al, Page, Henderson pabis, logarithmic, Newton and modified Page models. Determination of constant values ​​using Microsoft Excel Solver Tools with input each drying model or equation used and curve fitting is carried out using non-linear regression analysis. The thin-layer drying model is obtained by finding the constant values ​​k, a and n of each model so that the best model for thin-layer drying of noni fruit is the page model for all temperatures with an R2 value at a temperature of 45 oC of 0.995 (RMSE 0.003), the R2 value at a temperature of 55 oC is 0.993, (RMSE 0.001) and at a temperature of 65 oC the R2 value is 0.992 (RMSE 0.000).